Expression of Resilience of Social Service Organizations in Lithuanian Regions - Gečienė, Jolita (Socialinė teorija, empirija, politika ir praktika, 2025)
The article examines how to strengthen the resilience of social service organizations in the regions of Lithuania when faced with extreme situations and unexpected events in the country. The research has established that, in order to overcome challenges and difficulties, social service organizations need to plan their actions in advance, quickly adapt to changes and strengthen resilience, which depends on factors that strengthen the resilience of social service organizations, such as: standardized risk management procedures, continuous strengthening of competencies, strategic planning, enabling leadership and management of business continuity processes. The research has identified measures to overcome difficulties: targeted staff involvement, inspiring organizational culture, effective risk and challenge management and the ability to adapt and maintain balance, while ensuring the continuity of activities. It has been revealed that the development of social services in the region is important for the resilience of social service organizations.
Keywords: social; organizations; resilience; Lithuania; regions